2013
DOI: 10.5120/12238-8446
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Neem Oil Methyl Esters Production using Artificial Neural Networks

Abstract: The objective of the present work is to develop models inculcating the effect of operating conditions of neem oil methyl esters (NOME) production in an oscillatory baffled reactor, namely temperature, time of reaction, oil to methanol ratio and catalyst concentration on the estimation of parameters like the viscosity of biodiesel produced by using Artificial Neural Networks technique. Experiments were conducted in the laboratory and the results obtained were used to develop the ANN model using MATLAB. The deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…These neurons are arranged in layers and are interconnected to one another. The beauty of ANN is that it is not compulsory for the user to know the relationship between the data processing elements beforehand in order to establish a correlation [34,35]. The input data are manipulated by the neurons and the interconnections of these neurons during each step of the process in order generate the output [36].…”
Section: Artificial Neural Network and Ant Colony Optimizationmentioning
confidence: 99%
“…These neurons are arranged in layers and are interconnected to one another. The beauty of ANN is that it is not compulsory for the user to know the relationship between the data processing elements beforehand in order to establish a correlation [34,35]. The input data are manipulated by the neurons and the interconnections of these neurons during each step of the process in order generate the output [36].…”
Section: Artificial Neural Network and Ant Colony Optimizationmentioning
confidence: 99%
“…The development of prediction methods are of great value in estimating properties of biodiesel. Relevant studies using ANN models have been found in recent literature . For example, Ramadhas et al .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bhattacharyulu et al . modeled the effect of operating conditions on the neem oil biodiesel viscosity using the ANN technique with an acceptable accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations